2008
DOI: 10.1080/00288230809510448
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sewage sludge and liming on productivity during the establishment of a silvopastoral system in north‐west Spain

Abstract: Silvopastoral systems are recognised as a sustainable means of increasing forest land through recovery of abandoned agricultural land. Establishment of agroforestry systems is currently promoted by the new EU regulations through direct farmer payments. This can fulfil Agenda 21's economic, cultural and social principles better than simply planting forest. An interesting fertilisation option for silvopastoral systems is sewage sludge, in view of the need to manage this product in environmentally acceptable ways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…Similar results have been reported by multiple authors following the application of sewage sludge to different tree species, including Douglas fir ( Pseudotsuga menziesii ) (Henry et al, 1994), Monterey pine ( Pinus radiate ) (López‐Díaz et al, 2009), and Canadian poplar ( Populus euramericana ) (Rigueiro‐Rodríguez et al, 2008). These authors showed that tree growth was inversely proportional to pasture production, especially when the pasture production was high due to fertilization (Campbell et al, 1994).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results have been reported by multiple authors following the application of sewage sludge to different tree species, including Douglas fir ( Pseudotsuga menziesii ) (Henry et al, 1994), Monterey pine ( Pinus radiate ) (López‐Díaz et al, 2009), and Canadian poplar ( Populus euramericana ) (Rigueiro‐Rodríguez et al, 2008). These authors showed that tree growth was inversely proportional to pasture production, especially when the pasture production was high due to fertilization (Campbell et al, 1994).…”
Section: Discussionsupporting
confidence: 87%
“…The responses of trees and pasture to fertilization depend on tree‐pasture interactions, which are in turn affected by soil conditions and the botanic composition of both the trees and the pasture (Rigueiro‐Rodríguez et al, 2008). Throughout the experiment, trees and pasture species responded favorably to the addition of sewage sludge.…”
Section: Discussionmentioning
confidence: 99%
“…The initial tree diameters in our study were also similar to those found by the same authors (15·3 mm). A positive effect was found for the ANA treatment in the two first years of the experiment; this trend has also been described for Populus × euroamericana (Rigueiro‐Rodríguez et al. , 2008b) and Pinus radiata D. Don, under soil conditions that were initially either very acid (López‐Díaz et al.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, the pasture production reduction observed in the last year could have been caused by competition with trees that were 147.92-175.16 cm in height and had a basal diameter of 4.19-5.17 cm, as light interception by the trees could potentially limit pasture development (Rigueiro-Rodríguez et al, 2008). After three consecutive years of sewage sludge application, Ló pez-Díaz et al (2007) observed that shade caused by 8-year-old trees (Pinus radiata) limited the effects of fertilisation (Balocchi and Phillips, 1997) and mineralization rate (Ló pez-Díaz et al, 2007) on pasture production.…”
Section: Discussionmentioning
confidence: 95%